Preliminary analysis of sodium experimental apparatus PLANDTL-2 for development of evaluation method for thermal-hydraulics in reactor vessel of sodium fast reactor under decay heat removal system operation condition - Ayako ONO (The Japan Society of Mechanical Engineers, 2020)
Fully natural circulation decay heat removal systems (DHRSs) are adopted for sodium fast reactors, which is a passive safety feature without any electrical pumps. It is needed to grasp the thermal-hydraulic phenomena in the reactor vessel and evaluate the coolability of the core under the natural circulation not only for the normal operating condition but also for severe accident conditions. In this paper, the numerical results of the preliminary analysis for the sodium experimental condition with the PLANDTL-2, in which the core and the upper plenum with a dipped-type direct heat exchanger (DHX) were modeled, are discussed to establish an appropriate numerical models for the reactor core including the gap region among the subassemblies and the DHX. The transient analysis simulating the reactor scram reveals that the 3-dimensional large scale flow structure is developed through the gaps in the whole of the core area during the reactor scram. The steady-state analysis coinciding Richardson number between the PLANDTL-2 and the reactor operation condition reveals that the hot spot and cold spot appear depending on the location of the DHX, which is caused by the complex thermal-hydraulic phenomena driven by the natural circulation. From these preliminary analyses, the characteristics of the thermal-hydraulics behavior in the PLANDTL-2 to be focused are extracted.